Prevention and treatment of ear diseases (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Among the organs of our body, in addition to the general function of hearing, the ear is an important organ that controls and maintains the body's sense of balance. In this article, we provide information about the origin of ear diseases, methods of prevention and treatment of diseases.